2014
DOI: 10.1063/1.4893928
|View full text |Cite
|
Sign up to set email alerts
|

Thermopower as a tool to investigate many-body effects in quantum systems

Abstract: Measuring the thermopower of a confined quantum system reveals important information about its excitation spectrum. Our simulations show how this kind of transport spectroscopy is able to extract a clear signal for the onset of Wigner localization in a nanowire segment. This demonstrates that thermopower measurements provide a tool for investigating complex many-body quantum effects, which is less intrusive than the usual charge-stability diagram as no high source-drain bias is required. While the effect is mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Recently, it turned out that the effects resulting from reduction of dimensionality can lead to increase of thermoelectric efficiency giving possibilities to create efficient heat-to-electric power converters [1][2][3][4] . Specifically, quantum dots seem to be good candidates for high-efficiency energy-converters as they reveal level and charge quantization which strongly affects the thermoelectric properties which has been shown theoretically [5][6][7][8][9][10][11][12][13][14][15][16] and observed in experiments [17][18][19][20][21] . Moreover, quantum interference effects in double quantum dots can additionally lead to large enhancement of thermoelectric response 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it turned out that the effects resulting from reduction of dimensionality can lead to increase of thermoelectric efficiency giving possibilities to create efficient heat-to-electric power converters [1][2][3][4] . Specifically, quantum dots seem to be good candidates for high-efficiency energy-converters as they reveal level and charge quantization which strongly affects the thermoelectric properties which has been shown theoretically [5][6][7][8][9][10][11][12][13][14][15][16] and observed in experiments [17][18][19][20][21] . Moreover, quantum interference effects in double quantum dots can additionally lead to large enhancement of thermoelectric response 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it turned out that the effects resulting from reduction of dimensionality can lead to increase of thermoelectric efficiency giving possibilities to create efficient heat-to-electric power converters 1-4 . Specifically, quantum dots seem to be good candidates for high-efficiency energy-converters as they reveal level and charge quantization which strongly affects the thermoelectric properties which has been shown theoretically [5][6][7][8][9][10][11][12][13][14][15][16] and observed in experiments [17][18][19][20][21] . Moreover, quantum interference effects in double quantum dots can additionally lead to large enhancement of thermoelectric response 22 .…”
mentioning
confidence: 95%
“…[3][4][5][6][7][8][9][10][11] Here the intrinsic advantage of thermoelectric measurements is that they probe asymmetries around the Fermi level and therefore can easily provide information about excited states. 12 Close to a degeneracy of energy levels in a quantum dot, interference and correlation effects can play an important role for transport and lead to pronounced quantum mechanical phenomena. For a spin-degenerate quantum dot (QD) the conductance experiences an enhancement for low temperatures due to the Kondo effect.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been recently demonstrated that thermopower measurements can serve as an interesting tool to characterize complex scenarios due to coherences and interactions in nanoscale systems [3][4][5][6][7][8][9][10][11]. Here the intrinsic advantage of thermoelectric measurements is that they probe asymmetries around the Fermi level and therefore can easily provide information about excited states [12].…”
Section: Introductionmentioning
confidence: 99%